Designing menus for healthy diets [videorecording] - Chua, Eu-Hua.; Video Education Australasia (Bendigo, Vic. Video Education Australasia, 2009)
This program looks at the function of food and shows how to understand the nutrients that require to maintain an adequate and well balanced diet. This also explore how nutritional requirements vary at different stages of the lifespan, and how to design menus that will fit in with the lifestyle and reflect a balanced diet in order to meet our needs. The program also looks at the impact that today's fast paced society has had with the growing trend of relying on convenience and fast foods as every day food choices.
VCD
Produced by Eu-hua Chua.
Keywords: Nutrition; Diet